2015
DOI: 10.12669/pjms.312.6816
|View full text |Cite
|
Sign up to set email alerts
|

An overview of smoking practices in Pakistan

Abstract: Smoking remains a major player in morbidity and mortality worldwide. It is a matter of immense public health importance as single leading cause of preventable deaths. The aim of this study was to assess smoking practices that prevail across Pakistan & Attitude of people towards this issue. We conducted an extensive search on major databases as well as search of bibliography of published literature for studies assessing Attitudes and Practices of tobacco smoking that prevail across Pakistan. Data from available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…In a survey conducted in Pakistan, 74% of smokers reported handling stress was the primary reason of smoking (37). Personal problems play a significant role in starting smoking and indicate that many young people fail to solve their problems.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey conducted in Pakistan, 74% of smokers reported handling stress was the primary reason of smoking (37). Personal problems play a significant role in starting smoking and indicate that many young people fail to solve their problems.…”
Section: Discussionmentioning
confidence: 99%
“…females (25). While another Pakistani study showed 21.6% as average national prevalence of cigarette smoking (26). Prevalence of smoking among adults in United States was 19% (27), while 19.3% in Iranian high school students, where 20.2% boys and 8.8% girls were smokers (28).…”
Section: Prevalence Of Smokingmentioning
confidence: 99%
“…Among the 500 respondents, a large ration of 90 percent respondents agreed to ban the smoking in the campus while 10 percent didn't agree to ban on smoking like stuff. (17) The above table illustrates the application of Lambda and Goodman and Kruskal tau test applied to the variables knowledge for the legislation and banning of Factors behind the Prevalence of Smoking the smoking in the college premises. Lambda test denotes that there is strong association between the knowledge for the legislation and banning of the smoking.…”
Section: Resultsmentioning
confidence: 99%